Desenvolvimento de metodologia para quantificação de praguicidas organofosforados em café por GC-MS e estudo da degradação durante a etapa de torra - Soares, Lara Cristina Teixeira (2012)
Coffee is one of the most important Brazilian crops, contributing significantly to the national economy. Currently Brazil is the largest coffee producer in the world and second largest consumer, the largest internal producer the state of Minas Gerais. To ensure a high production, farmers apply pesticides on these crops. Among these pesticides, one of the most used is disulfoton, an organophosphate insecticide, systemic and highly toxic. Pesticides undergo natural degradation/ transformation when exposure to the environment; therefore they can generate either products more toxic than the original or can degrade to simple inorganic compound. The most widely used techniques for identification of pesticides are chromatographic techniques coupled to mass spectrometry (GC-MS and LC-MS). Regarding those techniques, sample preparation is required before analysis. The QuEChERS preparation method has many advantages, for instance, it consumes small amount of solvents, provides quick preparation, is efficiency and has robustness of results. Despite these advantages, there are no published reports regarding the sample preparation of roasted coffee. In this report a sample preparation methodology was developed and optimized, based on the QuEChERS method and analysis by GG-MS, in order to evaluate the contamination of coffee with the pesticide disulfoton and its products (sulfoxide and sulfone), subsequently introducing new pesticides in that analysis. Additionally, we tested substances called "analyte protectants”, which have the capacity of preventing degradation of the compounds of interest into the GC system. From the optimized method, it was made a validation, according to protocols from residual control agencies. Real samples were analyzed and no pesticide residues were detected in those samples. The persistence of contaminants was also observed throughout the roasting step, monitoring the roasting time and end temperature, being verified that total degradation of the analytes were achieved after the sixth minute of roasting. With the obtained results the method showed to be adequate to rapid and simple sample preparation of complex samples, before the GC-MS analysis step.